2020
DOI: 10.1093/brain/awaa365
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic imaging and clinical predictors for phenoconversion of REM sleep behaviour disorder

Abstract: This is an international multicentre study aimed at evaluating the combined value of dopaminergic neuroimaging and clinical features in predicting future phenoconversion of idiopathic REM sleep behaviour (iRBD) subjects to overt synucleinopathy. Nine centres sent 123I-FP-CIT-SPECT data of 344 iRBD patients and 256 controls for centralized analysis. 123I-FP-CIT-SPECT images were semiquantified using DaTQUANTTM, obtaining putamen and caudate specific to non-displaceable binding ratios (SBRs). The following clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 27 publications
8
96
0
Order By: Relevance
“…Additionally, a progressive decline in striatal binding in patients with iRBD further support the notion that RBD is actually an integral prodromal period of a defined neurodegenerative syndrome [ 182 ]. Several recent studies confirmed the high sensitivity of abnormal DAT-SPECT to accurately predict the short-term conversion to a clinically-defined α-synucleinopathy [ 183 , 184 , 185 , 186 , 187 ].…”
Section: Dat Imaging As Preclinical Biomarkermentioning
confidence: 88%
“…Additionally, a progressive decline in striatal binding in patients with iRBD further support the notion that RBD is actually an integral prodromal period of a defined neurodegenerative syndrome [ 182 ]. Several recent studies confirmed the high sensitivity of abnormal DAT-SPECT to accurately predict the short-term conversion to a clinically-defined α-synucleinopathy [ 183 , 184 , 185 , 186 , 187 ].…”
Section: Dat Imaging As Preclinical Biomarkermentioning
confidence: 88%
“…Rapid eye-movement sleep behavior disorder (RBD) is a parasomnia disorder that involves violent and undesirable behaviors [ 1 ] such as physical reactions to dreams due to the loss of normal muscle atonia during rapid eye movement (REM) sleep. RBD can occur alone (idiopathic RBD—iRBD) or in association with other neurological disorders (symptomatic RBD) [ 2 ], and people with iRBD have a high risk of developing Parkinson’s disease (PD), dementia with Lewy bodies (DLB), and multiple systemic atrophy [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, recent studies have suggested that 'isolated RBD (iRBD)' reflects the early phase of later development of neurodegenerative changes, as the concept of 'prodromal parkinsonism' has been suggested to represent an early expression of α-synucleinopathy [7]. According to the results of recently published prospective studies, the phenoconversion rate from iRBD to parkinsonism or dementia are similar [8,9].…”
Section: Introductionmentioning
confidence: 99%